2012
DOI: 10.7763/ijiee.2012.v2.133
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis with Ternary Difference: Applied to BlockCipher PRESENT

Abstract: Signed difference approach was first introduced by Wang for finding collision in MD5. In this paper we introduce ternary difference approach and present it in 3 symbols. To show its application we combine ternary difference approach with conventional differential cryptanalysis and apply that to cryptanalysis the reduced round PRESENT. We also use ant colony technique to obtain the best differential characteristic. To illustrate the privilege in the result of experiment, we calculate advantage of the attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We have also shown that one can recover at the most 30 subkey bits by the differential attack with the success probability of 0.999999904. Lots of work has been done and is being done in [6], [7], [8], [9] on the basis of this differential attack given by Wang [3] assuming to recover 32 subkey bits of 16 round PRESENT, therefore the rectifications made out to come to the conclusion that the number of subkey bits recoverable by this attack is exactly 30 and not 32 as claimed earlier is very important for further research.…”
Section: Resultsmentioning
confidence: 99%
“…We have also shown that one can recover at the most 30 subkey bits by the differential attack with the success probability of 0.999999904. Lots of work has been done and is being done in [6], [7], [8], [9] on the basis of this differential attack given by Wang [3] assuming to recover 32 subkey bits of 16 round PRESENT, therefore the rectifications made out to come to the conclusion that the number of subkey bits recoverable by this attack is exactly 30 and not 32 as claimed earlier is very important for further research.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is worth noting that alternative types of operations may also be contemplated. For example, Berson introduces the modular difference to study the MD/SHA family of hash functions [7], and similar method has been used [8] to cryptanalyze the block cipher PRESENT [9]. Borisov et al [10] proposed a new type of differential known as multiplicative differential to attack IDEA [11].…”
Section: Introductionmentioning
confidence: 99%